Oligodontia and Facial Phenotype Associated with a Rare Syndrome - Fatima Ezzahra Zidane; Mustapha El Alloussi (Case Reports in Dentistry)
Introduction. Oligodontia is a dental abnormality in which the patient is missing teeth. It is a hereditary disorder characterized by agenesis of more than six primary or permanent teeth, excluding the wisdom teeth. Oligodontia is often related with an abnormal size of teeth, conical shape, taurodontism, frequent enamel abnormalities, and delayed eruption. Oligodontia may be clinically isolated or associated with ectodermal dysplasia, a large group of rare diseases, and other syndromes. Patient Information. Dental characteristics of a six-and-a-half-year-old Moroccan boy with oligodontia and in apparent good health were described. Clinical Findings. Three syndromes associated with oligodontia have been discussed. Above all, based on the facial phenotype, Dubowitz syndrome has been retained as the most likely diagnostic hypothesis. This case could be the first reported case described in Morocco, but a thorough examination with genetic analysis must be carried out. Conclusion. Oligodontia could clinically be isolated or associated with ectodermal dysplasia, a large group of rare diseases, and other syndromes.